PENGARUH MEDIA VIDEO ANIMASI TERHADAP PENGETAHUAN IBU HAMIL TENTANG STUNTING DI PUSKESMAS MEGANG - Sari, Novia; Qoiriyah, Siti; Ayu Mustika Handayani (LPPM STIKes Mitra Adiguna, 2025)
Stunting in toddlers in developing countries can be caused by genetic factors and environmental factors that are inadequate for child growth and development. Risk factors for stunting are nutritional status, environmental cleanliness, complementary foods, exclusive breastfeeding, birth weight, parental education, parental income, diarrheal infectious diseases and feeding patterns. Pregnant women's knowledge about stunting is the most basic thing as an effort to prevent stunting, because pregnancy is the golden period of 1000 HPK. The purpose of this study was to determine the effect of animated video media on pregnant women's knowledge about stunting at the Megan Health Center. This study is a pre-experimental study using the one group pretest posttest design research method. The study was conducted from July 2024 to December 2024. Sampling using a simple random sampling method so that 43 pregnant women were obtained. The analysis of this study was carried out using univariate and bivariate analysis using the paired t-test. The results of the study showed that the average knowledge of pregnant women before health education using animated video media was 7.40. then after the intervention the average knowledge of mothers was 12.67. There is an influence of animated video media on pregnant women's knowledge about stunting with a p-value <0.001. Health education using animated video media can be used as a health promotion media in increasing pregnant women's knowledge about stunting so it needs to be optimized in its implementation.